Analysis of the Manuscript and Methodology of Imam Syafi'i's Musnad: A Study of the Mujtahid's Monumental Work - Devi Ganis Prameswari; Muhammad Albaqir; Rizzaldy Satria Wiwaha; Irwan Abdurrahman; Neni Nurlaela (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to comprehensively examine the characteristics and methodology of Musnad Imam Syafi'i, the work of Sheikh Muhammad 'Abid al-Sindi, which compiles the basic hadiths of Imam Syafi'i's legal arguments. This study was conducted to answer the academic need to understand the authenticity, structure, and role of the book in the development of hadith science in the 2nd century Hijriah. This study uses a qualitative, codicological and historical-descriptive approach. Primary data comes from the modern tahqiq edition of Musnad Imam Syafi'i, while secondary data are obtained from classical works such as Tarikh Baghdad (al-Khatib), Siyar A'lam al-Nubala' (al-Dzahabi), and Tahdzib al-Asma' wa al-Lughat (al-Nawawi). Data collection techniques were carried out through documentary studies and text analysis, while data analysis was carried out by analyzing the content of sanad-matan criticism, as well as verification of other works of Imam Syafi'i such as al-Umm. It was found that the Musnad of Imam Shafi'i was compiled based on the companions of the narrators, and focused on the ahadith al-ahkam. The methodology of this book demonstrates a balance between the authenticity of the sanad and legal rationality, emphasizing Imam Shafi'i's role as a link between the early tradition of hadith transmission and the textual and rational Islamic legal system. This study confirms the significance of the Musnad of Imam Shafi'i in the study of hadith and the Shafi'i school of thought, and offers a new approach by combining the study of codicology and hadith criticism to contribute to the study of methodology and the preservation of classical Islamic treasures.